Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Amun: nouvelles - Jean, Michel (Stanké, une société de Québecor média, 2016)
« Dans la langue innue, amun signifie « rassemblement ». Sous la direction de Michel Jean, écrivain et journaliste innu, ce collectif brûlant d'actualité réunit des auteurs autochtones de divers horizons, de différentes nations et générations. Leurs nouvelles, variées, reflètent non seulement l'histoire et les traditions, mais aussi la réalité des Premières Nations au Québec et au Canada. Offrant à lire les points de vue d'artistes de renom, ce livre est le théâtre d'un rassemblement qui ne se fait que trop rarement. »–Quatrième de couverture.
Les nouvelles de Fontaine, Natacha Kanapé, 2016. « J’ai brûlé toutes les lettres de mon prénom » et de Cousineau-Mollen, Maya, 2016. « Mitatamun (Regret) » ont été données en lecture au cours SEX2283
Keywords: amériques; appartenance; approches et analyses; arts; canada; cours; discipline; environnement; féminisme autochtone; littérature; littérature autochtone; pensionnats; premier cycle; premières nations; québec; racisme; régions géographiques; sex2283; spiritualité; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires

Agir avec le désespoir environnemental - Macy, Joanna (Reclaim : recueil de textes écoféministes, 2016)
Keywords: EDI; amériques; approches et analyses; cours; discours dominant; environnement; fem1000; fem3600; justice sociale; mouvements sociaux; pratiques féministes; premier cycle; régions géographiques; systèmes d'oppressions; thématiques; écoféminisme; écopsychologie; états-unis